The effect of input sensory modality on the multimodal encoding of motion events - Mamus, E; Speed, LJ; Özyürek, A; Majid, A (Taylor and Francis, 2022)
Each sensory modality has different affordances: vision has higher spatial acuity than audition, whereas audition has better temporal acuity. This may have consequences for the encoding of events and its subsequent multimodal language production—an issue that has received relatively little attention to date. In this study, we compared motion events presented as audio-only, visual-only, or multimodal (visual + audio) input and measured speech and co-speech gesture depicting path and manner of motion in Turkish. Input modality affected speech production. Speakers with audio-only input produced more path descriptions and fewer manner descriptions in speech compared to speakers who received visual input. In contrast, the type and frequency of gestures did not change across conditions. Path-only gestures dominated throughout. Our results suggest that while speech is more susceptible to auditory vs. visual input in encoding aspects of motion events, gesture is less sensitive to such differences.